João Gilberto Noll e a subversão do real (representação, deslocamentos e permanência em O quieto animal da esquina e Harmada) - Silva, Efraim Oscar (Universidade Federal de São Carlos, 2015)
This master thesis discusses the real s representation on João Gilberto Noll s novels O quieto animal da esquina (1991) and Harmada (1993). Firstly, it focuses on the ways of representing the real in the classic, the modern and the contemporary novel as well as aspects from Realism and Naturalism in the Brazilian literature, emphasizing the existence of a social criticism tradition in this literature. Then, this study deals with structural questions related mainly to the narrative focus, time and space, questioning the last ones also based on some readings on anthropology, psychology and geography. This procedure intends to show that O quieto animal da esquina and Harmada keep formal and thematic features proper to the classic and the modern novel realistic representation. At the same time, they make a shift on this representation by reformulating, creating a tension and subverting themes and narrative instances in order to express, in a singular diction and throughout the time and space immobility of the represented individuals, the disaggregation and the lack of collective ideals that characterize the contemporary Brazilian society.
Keywords: Literatura; Noll, João Gilberto, 1946-; Realismo; João Gilberto Noll; O quieto animal da esquina; Harmada; Representação do real; Narratologia; Crítica social; Real s representation; Realism; Narratology; Social criticism; LINGUISTICA, LETRAS E ARTES::LETRAS